2014
DOI: 10.1038/ngeo2200
|View full text |Cite
|
Sign up to set email alerts
|

Eddy-induced variability in Southern Ocean abyssal mixing on climatic timescales

Abstract: The Southern Ocean plays a pivotal role in global ocean circulation and climate [1][2][3] . It is there that the deep water masses of the world ocean upwell to the surface and subsequently sink to intermediate and abyssal depths, forming two overturning cells that exchange large amounts of heat and carbon with the atmosphere [4][5][6] . While the climatic drivers of changes in the upper cell are relatively well established 7 , little is known about how the lower cell responds to changes in climatic forcing. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 32 publications
5
53
1
Order By: Relevance
“…Both Sheen et al (2014) and Waterman et al (2014) showed that the shear based parameterization overestimates observed mixing rates in near-bottom regions of strong internal wave generation. The parameterization relies on the assumption that the background internal-wave field is well characterized by the Garrett-Munk (GM) spectrum.…”
Section: Estimates Based On Finestructure Shearmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Sheen et al (2014) and Waterman et al (2014) showed that the shear based parameterization overestimates observed mixing rates in near-bottom regions of strong internal wave generation. The parameterization relies on the assumption that the background internal-wave field is well characterized by the Garrett-Munk (GM) spectrum.…”
Section: Estimates Based On Finestructure Shearmentioning
confidence: 99%
“…Ledwell et al (2010), St. Laurent et al (2012), and Sheen et al (2014) showed that enhanced internal wave fine-structure and turbulence levels were not widespread, but limited to frontal zones where strong bottom currents collide with steep large-amplitude topography. This thesis uses data primarily from two field expeditions of the DIMES study, hereafter referred to as the US2 and US5 expeditions (Fig 1-10 and 1-12).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct measurements of dissipation made as part of the DIMES study are described by Ledwell et al (2011), St. Laurent et al (2012, and Sheen et al (2014). These studies showed that enhanced internal wave fine structure and turbulence levels were not widespread but were limited to frontal zones where strong bottom currents collide with significant topography.…”
Section: Introductionmentioning
confidence: 99%
“…This scarcity of in situ data is particularly pronounced in the Southern Ocean. Despite the significance of the Southern Ocean to ocean-atmosphere CO 2 exchange and global climate, and the important role of ocean eddies to these pro- cesses (Frenger et al, 2013;Sheen et al, 2014;Morrow et al, 1994), it remains a remote, hostile and under-sampled ocean environment.…”
Section: Introductionmentioning
confidence: 99%